2005
DOI: 10.1243/095440505x32788
|View full text |Cite
|
Sign up to set email alerts
|

An inter-enterprise semantic web system to support information autonomy and conflict moderation

Abstract: This paper discusses a semantic web architecture for formation of an extended project team manufacturing system engineering moderator (EEMSEM) which includes four major modules: ontology acquisition, ontology mapping, knowledge acquisition, and design moderation. This collaborative system architecture focuses on how to support information autonomy that allows individual enterprises to keep their own preferred terminology or languages rather than requiring them to adopt a single standardized vocabulary. Differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 6 publications
0
16
0
Order By: Relevance
“…The Collaboration Moderator Service (CMS) develops earlier Moderator research (Harding et al, 2003;Lin et al, 2005) and applies it to support VOs. The aim of CMS is to raise awareness of opportunities or potential problems and the needs, possible consequences and likely outcomes in collaboration activities between the partners of a VO.…”
Section: Collaboration Moderator Services Structurementioning
confidence: 99%
“…The Collaboration Moderator Service (CMS) develops earlier Moderator research (Harding et al, 2003;Lin et al, 2005) and applies it to support VOs. The aim of CMS is to raise awareness of opportunities or potential problems and the needs, possible consequences and likely outcomes in collaboration activities between the partners of a VO.…”
Section: Collaboration Moderator Services Structurementioning
confidence: 99%
“…Ontologies are conceptualizations of a domain in a form which can be understood by all the agents involved and by careful design they can remove ambiguity from the communication language. The detail and design of such ontologies are beyond the scope of this research; however, details can be found in Lin et al [66]. The interface agent translates the messages received from the knowledge agent from the common format into the local format based on the ontology and also converts the messages from the DMA into the common format before transmitting them to the knowledge agent.…”
Section: Data Mining Agentmentioning
confidence: 99%
“…The MSE ontology defined in Lin's research has been converted into a formal ontology language, a resource description framework and a resource description framework schema, to serve as ontology metadata that may be used to create delete, modify and query the MSE ontology. A method of ontology inference was proposed by building sets of declarative mapping rules that could be applied to map all the shareable semantic metadata between the common MSE ontology and any manufacturing system models to enable semantic and syntax integration [54,56,57]. The MSE Ontology model has been captured in seven top level classes (Prq1*ect, Flow, E-%-tended Enter prise, Enter pfise, Process, Resource, and Strate using the knowledge and : 9Y) experience published in manufacturing system information models [41,42,[58][59][60].…”
Section: Extended Enterprise/e-supply Chain Moderatormentioning
confidence: 99%
“…The consequent enormous amounts of heterogeneous data (e. g. structural heterogeneity or semantic heterogeneity) make it increasingly difficult to communicate between different project teams and organizations. In response to this problem and to achieve true information interoperability, Lin et al [55] adopted the ontology and semantic web technologies within a Manufacturing System Engineering Moderator (MSEM) to enable semantic Interoperability across extended project teams [57].…”
Section: Universal Knowledge Moderator For E-supply Chainmentioning
confidence: 99%
See 1 more Smart Citation